Factors Influencing Purchasing Behavior in Shopping Malls in Kathmandu Valley - Manandhar, Raju Bhai; Timilsina, Jagat (PYC Nepal Journal of Management, 2022)
The shopping mall concept has been a great success in delivering various products available under one roof. The present shopping trend has gradually shifted from grocery stores to shopping malls. The objective of the study was to measure the association and effect of advertising and the purpose of visits on purchasing behavior in the shopping malls among Nepalese consumers. The current research is descriptive and analytical. The participants in the study were from Kathmandu valley residents who frequently visited shopping malls. The sample size was 384. The convenience sampling technique was adopted to choose respondents. The survey questionnaire was used to collect primary data on a six-point Likert scale. The data were analyzed using mean, standard deviation, independent sample, t-test, correlation, and regression analysis. The study discovered that advertising has an association but does not significantly influence purchasing behavior in shopping malls. The study also found that the purpose of visits has an association with and influences purchasing behavior in the shopping mall. In addition, gender effect only on purpose to visit but not advertising and purchasing behaviour at the shopping mall. Future researchers can investigate other factors that influence purchasing decisions in the shopping mall.